2015
DOI: 10.1038/ajg.2015.152
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of Genetic Mutations at Key Loci Predicts Progression to Esophageal Adenocarcinoma in Barrett’s Esophagus

Abstract: OBJECTIVES:Risk stratification in Barrett's esophagus (BE) is challenging. We evaluated the ability of a panel of genetic markers to predict progression to high-grade dysplasia (HGD) or esophageal adenocarcinoma (EAC).METHODS:In this case–control study, we assessed a measure of genetic instability, the mutational load (ML), in predicting progression to HGD or EAC. Cases had nondysplastic BE or low-grade dysplasia (LGD) at baseline and developed HGD/EAC ≥1 year later. Controls were matched 2:1, had nondysplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 50 publications
1
32
0
2
Order By: Relevance
“…The extent of genomic instability, measured as the mutational load in a biopsy of BE, can predict the risk of progression of BE to EAC in patients who otherwise would have been deemed low risk on the basis of histological findings alone. Mutational load summarizes the presence and clonality of loss of heterozygosity (LOH) mutations and the emergence of new alleles, manifested as microsatellite instability (MSI) mutations, in ten genomic loci around tumor suppressor genes associated with EAC (28,29).…”
Section: Barrett's Esophagus (Be)mentioning
confidence: 99%
“…The extent of genomic instability, measured as the mutational load in a biopsy of BE, can predict the risk of progression of BE to EAC in patients who otherwise would have been deemed low risk on the basis of histological findings alone. Mutational load summarizes the presence and clonality of loss of heterozygosity (LOH) mutations and the emergence of new alleles, manifested as microsatellite instability (MSI) mutations, in ten genomic loci around tumor suppressor genes associated with EAC (28,29).…”
Section: Barrett's Esophagus (Be)mentioning
confidence: 99%
“…Biomarker panels have been used in recent years to determine the risk of dysplasia and neoplasia in the setting of BE . Such methods include examining gene methylation arrays and mutational load . Recently, a systematic review suggested a possible role for p16 hypermethylation as an individual epigenetic biomarker in predicting BE progression to EAC .…”
Section: Recent Advances In Diagnostic Surveillance In Be Dysplasiamentioning
confidence: 99%
“…26 The mutational load score was compared between 23 patients with non-dysplastic Barrett’s esophagus or those with LGD who progressed to HGD/cancer and 46 patients with non-dysplastic Barrett’s esophagus or those with LGD who did not progress. The mutational load score was significantly higher in patients who progressed to HGD/cancer than in patients who did not.…”
Section: Use Of Biomarker Panels To Assess Cancer Risk In Barrett’s Ementioning
confidence: 99%